World sugar trade statistics 1987-1996 (F.O. Licht GmbH Tunbridge WellsGB, 1997)
Provides statistics on the world sugar imports and exports, as well as the sugar imports; raw sugar imports; white sugar imports; sugar exports; raw sugar exports; and, white sugar exports of individual countries where applicable.
DC